An alternative path to modernity the Sephardi diaspora in Western Europe - Ḳaplan, Yosef 1944- (Leiden [u.a.] Brill, 2000)
The essays in this book depict the social and intellectual ferment of the former Marranos from Spain and Portugal who returned to the fold of Judaism in Western Europe during the seventeenth century and established new Jewish communities in Amsterdam, Hamburg and London.
Literaturangaben
Archivierung prüfen
Archivierung prüfen
Keywords: Sephardim -- Europe, Western -- History -- 17th century; Jews -- Europe, Western -- History -- 17th century; Marranos -- Netherlands -- Amsterdam -- History -- 17th century; Jews -- Ethnic relations; Europe, Western -- Ethnic relations; Aufsatzsammlung